2019
DOI: 10.1111/jfpp.14059
|View full text |Cite
|
Sign up to set email alerts
|

Determining protein denaturation of sardine (Sardina pilchardus) marinates before and after the maturation

Abstract: In this study, sardine fish (Sardina pilchardus) was subjected to marination at different degrees of acidity (2.5%–5%). On the basis of the duration of maturation (22 days) and postmaturation period (three months after maturation), protein denaturation and quality changes of marinades were determined. Quality parameters, such as pH, acidity, salinity, and lipid oxidation, were examined for both periods. As a result of the study carried out for 22 days at different acidity levels, the change in the amount of TV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In accordance with the previously presented results regarding the thermal stability of miyofibrillar protein, the energy required for the proteins denaturation gradually increased in an age-related manner, and then decreased at a similar rate. These increases may indicate inhibition of proteolytic enzymes in denaturation, reduction in enthalpy and lower peaks at higher temperatures, denaturation of fillet proteins [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In accordance with the previously presented results regarding the thermal stability of miyofibrillar protein, the energy required for the proteins denaturation gradually increased in an age-related manner, and then decreased at a similar rate. These increases may indicate inhibition of proteolytic enzymes in denaturation, reduction in enthalpy and lower peaks at higher temperatures, denaturation of fillet proteins [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Heating was applied from 20 °C to 90 °C with a heating rate of 5 °C/min using an empty container placed in the sample device and sealed in the same way as a reference. The thermal changes of the analyzed samples were acquired on thermogram [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported the changes in the structure and physicochemical properties of myofibrillar protein during storage, suggesting that protein denaturation is a major contributor of shelf-life decline, nutrient loss, and structural changes in fish (Alak et al, 2021;Isık et al, 2020). Protein oxidation is a complicated phenomenon that involves amino acid residues, buried hydrophobic exposure, and protein unfolding upon heating (Dericioglu at al., 2019). This process leads to further chemical modifications in amino acid side chains, triggers polymerisation, disruption of peptide backbones, and following aggregation, it involves intermolecular protein…”
mentioning
confidence: 99%